If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/7(6x+4)=x
We move all terms to the left:
1/7(6x+4)-(x)=0
Domain of the equation: 7(6x+4)!=0We add all the numbers together, and all the variables
x∈R
-1x+1/7(6x+4)=0
We multiply all the terms by the denominator
-1x*7(6x+4)+1=0
Wy multiply elements
-7x^2(6+1=0
| 36=12^2x^+1 | | 6(x−5)=12 | | 2x-3=72 | | 2x+3.50=11.50 | | 36=12^2x+1 | | 4x2+9=7 | | 2x+3.50=11 | | 7x+500+5x=515 | | 1/3p+7=28 | | 16/20=4/y | | 5(2x−8)=20 | | 1/x+1/5=1/3 | | 11x+2(60-2x)=225 | | 1/15x=2/15 | | 11x-2(60-2x)=225 | | 11x+77(60-2x)=225 | | 140.39/65.6=x/85 | | 4(2z−5)=−4 | | 30/32=n | | 6x^2+20=-4 | | 8(y−9)=-32 | | 2.94k+2.94-1=7.82 | | 4(h-2)=16 | | (46-15/3+28)=a | | 2q+2-5.8=4.2 | | 6=30+4x | | 6+4x=30+4x | | –(x-4)=2x+6 | | 8x-(2x-9)=-3 | | m-13.12/3=1.34 | | 1.1x-0.27=1.05 | | 4(4-w)=(2w+2) |